STRATEGIC ALLIANCE IN THE CONSTRUCTION INDUSTRY: BARRIERS FACING ITS IMPLEMENTATION IN AN EMERGING MARKET - Funmilayo Iyabo BODUNDE; Ebunoluwa Akinrata; Ayodeji Emmanuel Oke; Ayotunde Babalola (Journal of Construction Project Management and Innovation)
Construction firms over the world involve in Strategy Alliance (SA) in order to achieve efficient time-cost-quality relationship during construction process through knowledge sharing, team culture and risk management with one another. Despite the numerous benefits gained, there are still various barriers facing it in the developing world. This paper is aimed at analysing the current level of awareness and barrier facing SA procurement method in the building industry in an emerging market (EM) using Nigeria as a case study, to profound future steps in avoiding these barriers and to encourage maximum implementation in the construction industry. A survey design was employed in evaluating the level of awareness of SA and barriers facing its adoption in building industry. Construction professionals in Nigeria were examined through a well-structured questionnaire. Mean Item Score and Factor Analysis were utilized in evaluating data gathered on the current barriers to SA procurement method in the construction industry. It was revealed from the study that the awareness level of SA procurement method within the industry amongst construction professionals is moderately high. This indicates that the barrier facing SA procurement method is not the issue of awareness but of willingness to adopt it. It was also established from the study that fear and trust issue, lack of strategic planning toward alliance, inadequate knowledge about alliance and, different in cultural values were the major component barriers facing strategic alliance procurement method. The study shows the true reflection of the current barriers facing the adoption of SA procurement methods in the developing country and notable points in this study can be largely recommended to promote strategic alliance partnership among construction firms the Nigerian construction industry and other emerging economy countries were building projects are carried out in the same approach, style and method.